Review in Pharmacokinetic Models on Corticosteroids - Semmar, Nabil; Simon, Nicolas (Mini Reviews in Medicinal Chemistry, 2006)
The pharmacokinetics of corticosteroids provides a large set of mathematical models which led to analyse many kinetic profiles corresponding to many clinical and/or physiological situations. In this paper, we present a review on the usefulness, advantages and limits of such models which could find a large application in medicinal chemistry.
Keywords: Pharmacokinetic models